KECEMASAN TERHADAP KETIDAKWAJARAN SKOR - NASWIATI NASWIATI (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2012)
The objective of this research is to find out the effect of students perception to physic, self regulated learning, and students’ anxiety toward the inappropriateness score test of physics. The data was collected through questionnaire and analyzed by using path analysis. The research found that as follows: 1) students perception to and students’ anxiety had positive direct effect toward inappropriateness score test achievement, and 2) students and self-regulated learning had positive direct effect toward students anxiety.